In vivo evidence for dendritic cell lysis by NK cells: Hints on improving cancer vaccines by targeting NK cell activation - Ferlazzo, Guido (Landes Bioscience, 2012)
By using an experimental model of anticancer vaccination, we have recently lent support to the assumption, so far only sustained by in vitro data, that natural killer cells can restrain less immunogenic, allegedly tolerogenic, dendritic cells (DCs). This in vivo selection of immunogenic DCs appears to depend on perforin and to be associated with a more protective tumor-specific T lymphocyte response.